2014
DOI: 10.1186/1744-8069-10-57
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Pattern of Changes in the Number of GAD65-Immunoreactive Inhibitory Terminals in the Rat Superficial Dorsal Horn following Peripheral Nerve Injury

Abstract: Inhibitory interneurons are an important component of dorsal horn circuitry where they serve to modulate spinal nociception. There is now considerable evidence indicating that reduced inhibition in the spinal dorsal horn contributes to neuropathic pain. A loss of these inhibitory neurons after nerve injury is one of the mechanisms being proposed to account for reduced inhibition; however, this remains controversial. This is in part because previous studies have focused on global measurements of inhibitory neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 49 publications
9
38
0
Order By: Relevance
“…GAD65 is another key rate-limiting-rate and is targeted preferentially to presynaptic terminals of central neurons for GABA synthesis (Tian et al, 1999;Patel et al, 2006). Studies have showed that GAD65 in different regions could participate in pain regulation by decreasing inhibition among neurons through reducing the levels of cellular GABA (Gwak and Hulsebosch, 2011;Zhang et al, 2011;Lorenzo et al, 2014). For example, suppression of Gad2 transcription through histone hypoacetylation in brainstem nucleus raphe magnus results in the impairment of GABA synaptic function and sensitized pain behavior (Zhang et al, 2011).…”
Section: Role Of Gad67 In the Spinal Dorsal Horn In Neuropathic Painmentioning
confidence: 99%
“…GAD65 is another key rate-limiting-rate and is targeted preferentially to presynaptic terminals of central neurons for GABA synthesis (Tian et al, 1999;Patel et al, 2006). Studies have showed that GAD65 in different regions could participate in pain regulation by decreasing inhibition among neurons through reducing the levels of cellular GABA (Gwak and Hulsebosch, 2011;Zhang et al, 2011;Lorenzo et al, 2014). For example, suppression of Gad2 transcription through histone hypoacetylation in brainstem nucleus raphe magnus results in the impairment of GABA synaptic function and sensitized pain behavior (Zhang et al, 2011).…”
Section: Role Of Gad67 In the Spinal Dorsal Horn In Neuropathic Painmentioning
confidence: 99%
“…In addition to changes in chloride gradient (Coull et al, 2003(Coull et al, , 2005 and decreased excitatory drive to inhibitory neurons (Balasubramanyan et al, 2006;Lu et al, 2009;Leitner et al, 2013), this may involve a loss of GABAergic terminals (Lorenzo et al, 2014) or reduced glycine release (Imlach et al, 2016). Tactile and innocuous information is carried by Ab fibers, which synapse primarily onto dorsal horn neurons in laminae III and IV (Abraira et al, 2017), whereas noxious information carried by C and Ad fibers is transmitted to the superficial laminae I and II (Peirs and Seal, 2016) (Fig.…”
Section: Altered Sensory Processing and Generation Of Allodyniamentioning
confidence: 99%
“…In spinal dorsal cord, GABAergic boutons appear to have relatively high levels of GAD65 and low levels of GAD67 (44). In neuropathic pain status, protein expression and mRNA of GAD reduce in the dorsal horn ipsilateral to the nerve injury in rats (45,46). Nerve injury induced reduction of GAD65 expression in spinal lamina I and lamina II.…”
Section: Disinhibition Of Spinal Gabaergic Interneurons and Neuro-patmentioning
confidence: 97%
“…Nerve injury induced reduction of GAD65 expression in spinal lamina I and lamina II. The greatest drop of GAD65 occurs in lamina II around 3-4 weeks after nerve injury (46). However, Moore et al (36) found that there was a significant depletion of GAD65, but not GAD67, in lamina II of the dorsal horn in animal model of neuropathic pain.…”
Section: Disinhibition Of Spinal Gabaergic Interneurons and Neuro-patmentioning
confidence: 99%